METODE PEMBELAJARAN AL-QUR’AN DALAM MENGINTERNALISASIKAN NILAI-NILAI AHKLAK QUR'ANI DI MA NURUL HASAN BRANI WETAN TAHUN AJARAN 2017-2018 - Soleha, Siti Amilus; Samsudin, Samsudin (BAHTSUNA: Jurnal Penelitian Pendidikan Islam, 2019)
ABSTRACT One aspect of religious education that is lacking attention is the education of reading the Qur'an. In general, parents are more focused on general education so that many Muslim children who can not read and write the Qur'an. As a first step is to lay a strong religious foundation on children in preparation for wading their lives and future lives. As where the word "pepetah learn as a child like carving on stone, learning as an adult like carving on water". Based on this problem, the teachers of the Qur'an must find a way out or enumeration. One of them is using methods that are interesting and easy to understand so that children and parents are interested in learning and entering their children in the Qur'anic education institution. But as far as the author is aware that there is still a need to improve the quality of the Qur'anic education. From these problems, in this study the author discusses the method of learning the Qur'an in Internalizing the values ​​of the Ahlak Qur'ani in MA Nurul Hasan Brani Wetan. Remembering children is the hope of parents, society, religion, and also the nation. Keywords: Al-Qur'an Learning Method, the value of the Qur'ani